The Role of Elisa test in the diagnosis of helicobacter pylori infection - Mohsun, Nassir E.; al-Hadithi, Raji H; saadallah, Suhaila (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Helicobacter pylori represents the major etiologic agent of gastritis, gastric and duodenal ulcer disease and can cause gastric cancer. Diagnostic testing for Helicobacter pylori can be divided into invasive and non-invasive techniques based upon the need for endoscopy. Serological test is one of the non – invasive tests although measuring these antibodies is not reliable method of diagnosis but may be used in certain condition.Objectives: To evaluate serum IgG antibodies against Helicobacter pylori by ELISA technique.Patients and Methods: The current study consisted of 115 patients (74 males, 41 females) attending The Gastrointestinal tract Center and Gastroscopy department in Baghdad Medical City and was subjected to gastroscopy, during the period from November 2004 to May 2005. Those how were examined for serum IgG against Helicobacter pylori by ELISA technique were compared with 10 apparently healthy individuals representing the control group.Results: By using the serological method (ELISA) 85 patients out of the 115 showed positive results (73.91%), however 7 out of the 10 individuals representing the control group were serologically positive (70%).Conclusion: Positive IgG antibody test for Helicobacter pylori indicates a marker for infection rather than an indicator for active infection.